Enhancing Early Childhood Self-Confidence Through a Play-Based Approach in Task Assignment - Nunik Ruliasari; I. Ismail (Manunggal Halim Jaya, 2026)
This study was motivated by the low level of self-confidence among early childhood students during learning activities, particularly when completing assigned tasks in Class A of TK Taswaja Sudimoro. Initial observations revealed that several children were hesitant to express their opinions, afraid of making mistakes, lacked the courage to perform in front of the class, and were not yet independent in completing tasks. This condition highlighted the need for a learning approach that aligns with the characteristics of early childhood education, namely learning through play-based activities. Therefore, this study aimed to improve children's self-confidence through a play-based approach in task assignments. This research employed the Classroom Action Research (CAR) method, which was conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were 13 children from Group A. Data were collected through observation, interviews, and documentation, and were analyzed using both descriptive quantitative and qualitative techniques. The results of the study indicated a significant improvement in children's self-confidence. The level of self-confidence increased from 45% in the pre-action stage to 65% in Cycle I and reached 85% in Cycle II. The children became more confident, independent, and actively engaged in learning activities. Thus, the play-based approach proved to be effective in enhancing the self-confidence of early childhood students at TK Taswaja Sudimoro.